Effects on hand-sheet paper properties of pH in deinking process - SÖNMEZ, SİNAN (My University, 2022)
In today\"s world where natural resources are rapidly decreasing, recycling printed papers, and their use in paper production will reduce the environmental pollution caused by waste paper. Thus, energy savings can be achieved with less energy consumption. Although many methods are used in the deinking of printed papers, the effectiveness of these methods varies depending on many parameters, such as the type of paper to be de-inked, the type of printed ink in the printing system, and the chemicals used in deinking. In this study, the effect of pH in the deinking process was studied. Electrophotographic printed papers were used as the printed paper in this study, and the INGEDE method was applied as the deinking method. In this method, 3 different pH environments were prepared and an ink removal process was carried out in this environment. Optical and physical properties were determined by producing hand-sheet papers from the deinked pulp. In addition, test prints were made to determine the printability of the produced hand-sheet papers in the electrophotographic printing system.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KAĞIT & AHŞAP; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, PAPER & WOOD; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; deinking; electrophotographic printing; INGEDE; pH; printability; recycle; WASTE; PULP; ENERGY